State Immunity Before the International Court of Justice: Jurisdictional Immunities of the State (Germany v Italy) - McMenamin, Matthew (Victoria University of Wellington Law Review, 2013)
The International Court of Justice recently gave judgment in Jurisdictional Immunities of the State. The case concerned German state immunity from civil claims brought in Italian courts by victims of serious violations of international humanitarian law committed by German armed forces during World War II. The Court offered a valuable clarification of the relationship between state immunity and jus cogens norms at customary international law. The conservative reasoning was thorough and extensive and the decision is likely to ossify the evolution of state immunity.